Debt Amongst Friends: Sympathy in Exchange and the Narration of a Transatlantic Credit Network, 1792–1837 - Borsk, Michael (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2019)
Conversations about credit in the transatlantic world were often suffused with accounts of feelings. More than just a warm gloss on the cold calculation of commerce in both merchant and settler economies, emotional exchanges played an integral role in the maintenance of credit relationships. The letters that circulated between John Large and his network of friends, family, and commercial contacts around the Atlantic reveal the importance of sympathy to his commercial relationships. Whether trading in the Caribbean and the United States or settling in Upper Canada, Large’s economic self-interest could never be excised from the wider world of sentimental sociability. As both a creditor and debtor, his economic undertakings were as concerned with hearts and souls as they were with trading balances and investment returns. In the world of transatlantic credit networks, sympathy was a colonial relationship, exchanged in commercial arrangements according to the ideal of friendship. Large’s correspondence, therefore, sits at the crossroads where credit’s moral economies met an expanding colonial capitalism during the eighteenth and nineteenth centuries.